Improving Timeliness in Surgical Discharge Summary Distribution: A Quality Improvement Initiative. Issue 4 (25th October 2022) - You, Peng; Liu, Jimmy; Moist, Louise; Fung, Kevin; Strychowsky, Julie E.
Abstract : Objective: To implement a quality improvement initiative to achieve an institutional targeted discharge summary distribution metric of 50% within 48 hours of patient discharge from hospital within an academic tertiary care otolaryngology–head and neck surgery department. Methods: A pre‐ and postintervention study was conducted. Process mapping was performed. Interventions included education and engagement, implementation of auto‐authentication (distribution immediately following transcription without review by the most responsible physician), and audit and feedback. The percentage of discharge summaries dictated with the auto‐authentication code was evaluated. Process measures were collected for 12 months pre‐ and postimplementation. Balancing measures included workload and revisions to auto‐authenticated notes. Analysis included summary statistics, statistical process control charting, and unpaired t tests. Results: The mean ± SD percentage of discharge summaries distributed within 48 hours increased from 19% ± 6.4% preintervention to 54% ± 20% postintervention ( P <. 0001). Seventy‐four percent of discharge summaries were dictated via the auto‐authentication code. The target metric was met in 71% of discharges with the auto‐authentication codes as compared with 26% with non–auto‐authentication. The interventions did not result in any change to perceived workload, and the incidence of auto‐authentication revisions was <1%. The results were sustained with an increase of 72% the following quarter. For fiscal year 2021‐2022, performance remained sustained with an 85% completion rate. Discussion: Our surgical department exceeded and sustained the targeted metric for timely discharge summary distribution using a quality improvement approach. Implications for Practice: Timely distribution of discharge summaries optimizes patients' transitions of care and can be achieved through stakeholder education and engagement, auto‐authentication, and audit with feedback.